PENGEMBANGAN PROFESIONALISME GURU ERA DIGITAL MELALUI PELATIHAN PEMBUATAN VIDEO KREATIF PEMBELAJARAN - Iqbal, M Iqbal Mustofa; Fathoni, Mukhamad; Rizki, Uli; Dwi Cahyani, Septia (Jurnal Abdi Insani, 2024)
This community service activity is based on the fact that many teachers feel confused when trying to create educational videos, even though creating educational videos is a prerequisite for teacher certification in today's professional landscape. The community service activity began with an observation, followed by a discussion forum to map out the issues found, which then served as the basis for determining the material to be delivered. The next phase involved training for the teachers, which was concluded with an evaluation. This training was held on December 16, 2023, in the computer lab at MTs Nurul Huda. The training was attended by 20 teachers from MTs Nurul Huda. The results indicated that teachers' competencies have improved, as evidenced by 10 out of 20 participants being able to independently create educational videos related to their subjects at MTs Nurul Huda.